Open Access journals published by Norwegian institutions – status and prospects - Karlstrøm, Henrik; Aspaas, Per Pippin (Septentrio Conference Series, 2021)
See RECORDING. More than 70 fully open-access, peer-reviewed journals are currently being published by government-funded service providers at eight Norwegian institutions. The service-providing staff is typically working within a research library, with the editor-in-chief affiliated to the same institution. In autumn 2020, Universities Norway (a cooperative body for accredited universities and university colleges in Norway), commissioned a report on this part of the national publishing landscape. The report was published in June 2021. As representatives of the committee writing the report, we present an overview of the Diamond Open Access publishing landscape in Norway and discuss our recommendations for strengthening the quality and robustness of the institutional service providers (ISPs). In brief, we suggest that the various ISPs merge and establish a board with an executive officer responsible for prioritizing technical upgrades and for establishing common standards and systems of quality assurance. Library staff at the various institutions should however still function as primary contacts for the editors and owners of the various journals, but operate according to clear guidelines and within a multi-institutional collegium.